Morphological and Behavioral Correlates of Long-Term Bird Survival in Selectively Logged Forest - Srinivasan, Umesh (Frontiers in Ecology and Evolution, 2019)
The response of biodiversity to land-use change has been a central focus in applied ecological research for close to half a century. However, despite a vast body of literature, our understanding of how species' traits influence demographic vital rates in anthropogenically-modified habitats is remarkably scant. Such an understanding is crucial because vital rates determine population viability in modified habitats, and underlie emergent occupancy, abundance and community-level patterns. I used capture-recapture analyses to estimate variation in survival of birds in intact and logged tropical montane forest in the eastern Himalayas. In general, variation in body mass and alternative behavioral strategies (e.g., mixed-species flocking vs. solitary behavior) were not associated with survival differences in intact forest. However, year-round residents, and species that did not participate in mixed-species flocks had appreciably lower survival in logged forest compared with intact forest. Solitary foragers, for instance, faced a 30% decline in survival in logged forest compared with intact forest. Non-migratory habit and solitary foraging behavior might make species vulnerable to extinction in logged forest through reduced survival, an especially important process in influencing population viability. Identifying how species' traits modulate their response to land-use change is crucial to predict population responses to forest modification, and to better plan and manage biodiversity-friendly forest use.